3S-hierarchical cluster-based energy-efficient data aggregation protocol in wireless sensor network. (28th July 2022) - Agarwal, Arun; Dev, Amita
Energy utilisation is one of the most common challenges in wireless sensor networks, as frequent communication between the sensor nodes results in a huge energy drain. To overcome this challenge, a 3S-hierarchical cluster-based energy-efficient data aggregation protocol in wireless sensor network is proposed, where 3S represents smart sensing, selective cluster head nomination, and data aggregation schedule which reduce the energy consumption for prolonging network lifetime. The proposed technique has three phases. Smart data sensing which uses an unbounded buffer to store data values and reduces transmissions. Cluster selection where high value nodes are treated as extended nodes to become candidate for cluster head selection. An advance aggregation schedule, which alternatively demands sensor nodes to send data buffer based on node identification value. Simulation analysis and the results proved that the proposed algorithm could effectively enhance the network lifetime and reduce energy consumption while maintaining acceptable packet delivery ratios and delay values.